Learning by Doing dalam Pendidikan Kewirausahaan : Studi Literatur terhadap Peningkatan Minat Berwirausaha Siswa Menengah Kejuruan - Dewi Amaliah Nafiati; Karinina Anyalir Putri; Nadia Khoirotun Nisa; Alvina Haryani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to systematically examine the role of learning by doing in entrepreneurship education in enhancing vocational high school students’ entrepreneurial interest through a literature study. The research method employed is a Systematic Literature Review (SLR) using the PRISMA protocol, in which data were collected from accredited journal databases (SINTA) published between 2021 and 2025 and analyzed using descriptive qualitative synthesis techniques. The findings indicate that practice-based learning approaches, such as Teaching Factory (TeFa) and project-based learning, significantly bridge the gap between theory and market realities, enhance students’ self-efficacy, and strengthen their entrepreneurial intentions. However, challenges such as limited facilities, teachers’ readiness, and unsystematic curriculum implementation remain obstacles in creating authentic learning experiences. Overall, this study confirms that experience-based learning innovation serves as a fundamental foundation for producing competitive and independent vocational school graduates in the digital economy era.